Using predictive modelling for forecasting blood donor response (International Journal of Engineering and Computer Science, 2017)
Blood and blood products are essential for medical treatment of all age groups. The primary source for blood products in the world is volunteer donors. Thus, donor recruitment and donor retention are vital factors for a blood bank to maintain its supply. We propose that developing a better understanding of donors' motivations to donate and personalizing their donation objectives would improve a blood bank's ability to secure a more robust supply of blood. The research paper puts forward a solution to predict whether a specific donor will donate blood in the coming month or not. This will help the blood banks to forecast their stock of various types of bloods and prepare accordingly.